2017
DOI: 10.1111/hae.13296
|View full text |Cite
|
Sign up to set email alerts
|

Co‐morbidities and bleeding in elderly patients with haemophilia—A survey of the German, Austrian and Swiss Society of Thrombosis and Haemostasis Research (GTH)

Abstract: The most common co-morbidity of the patient population was hypertension, a considerable part had ischemic heart disease and antiplatelet or anticoagulant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 29 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…23,29 The proportion of deaths from HIV varied widely, from 1% in 2000 through 2010 in a study of people with non-severe HA in Europe/Australia, to 55.9% in 1980 through 1989 in an Italian study of PwH. 23,26 Seven studies reported a peak of HIV-related deaths during the AIDS epidemic in the late 1980s and early 1990s ( Figure 2B), 23,25,28,29,33,36 which decreased from then on. [23][24][25][26]31,33,35 The proportion of deaths due to HCV/HBV infection or hepatic disease ranged from 6% (severe hemophilia) to 32% (severe hemophilia without FVIII inhibitors).…”
Section: Virus-related Deathsmentioning
confidence: 99%
See 4 more Smart Citations
“…23,29 The proportion of deaths from HIV varied widely, from 1% in 2000 through 2010 in a study of people with non-severe HA in Europe/Australia, to 55.9% in 1980 through 1989 in an Italian study of PwH. 23,26 Seven studies reported a peak of HIV-related deaths during the AIDS epidemic in the late 1980s and early 1990s ( Figure 2B), 23,25,28,29,33,36 which decreased from then on. [23][24][25][26]31,33,35 The proportion of deaths due to HCV/HBV infection or hepatic disease ranged from 6% (severe hemophilia) to 32% (severe hemophilia without FVIII inhibitors).…”
Section: Virus-related Deathsmentioning
confidence: 99%
“…Nine observational studies published between 2010 and 2020 reported on crude mortality rates and/or mortality ratios; the data in TA B L E 3 Overview of studies reporting cause of death [22][23][24][25][26]28,29,[31][32][33][34][35][36][37][38] these studies spanned 1968 through 2018. [23][24][25][26][27][28][29][30][31] The mortality ratio Table 1).…”
Section: Mortality Rates and Ratiosmentioning
confidence: 99%
See 3 more Smart Citations